Jonathan Gruber’s “Public Finance and Public Policy”: A Critical Analysis - Mohammad Javad Sharifzadeh (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The idea of the proper role of the public sector (the state) in the economy has been discussed from the ancient times and due to its importance has entered the educational programs of universities around the world. This paper introduces and critically analyses Jonathan Gruber’s Book entitled “Public Finance and Public Policy”. The book is one of the most recent textbooks in the field and is used as the main textbook in the public sector economics courses in many universities. The main strengths of the book are: fulfilling the formal standards of textbooks, up-to-date contents, the author’s emphasis on the practical and experimental issues of the public finance, its logical order, and its very user friendly writing. But, the book has some important shortcomings such as: its emphasis on the Pareto approach and neglecting alternative approaches such as the Rawlsian approach or the Amarya sen`s capability approach, lack of care to the historical approach and issues, neglecting non-liberal economists’ theories (e.g. socialist theories), neglecting the specific issues of the public finance in developing countries and ignoring new scientific instruments and issues such as game theory and behavioral public finance.